Analysis of single nucleotide polymorphisms in the NOS2A gene and interaction with smoking in age-related macular degeneration - AYALA-HAEDO, JUAN A. (2010)
Age-related macular degeneration (AMD) is a complex degenerative retinal disease influenced by both genetic and environmental risk factors. We assessed whether single nucleotide polymorphisms (SNPs) in the NOS2A gene increase risk and modulate the effect of smoking in AMD. 998 Caucasian subjects (712 AMD cases and 286 controls) were genotyped for 17 SNPs in NOS2A. Multivariable logistic regression models containing SNP genotypes, age, sex, smoking status and genotype/smoking interaction were constructed. SNP rs8072199 was significantly associated with AMD (OR = 1.3; 95% CI : 1.02, 1.65; P = 0.035). A significant interaction with smoking was detected at rs2248814 (P = 0.037). Stratified data by genotypes demonstrated that the association between AMD and smoking was stronger in carriers of AA genotypes (OR = 35.98; 95% CI: 3.19, 405.98) than in carriers of the AG genotype (OR=3.05; 95% CI: 1.36, 6.74) or GG genotype (OR=2.1; 95% CI: 0.91, 4.84). The results suggest a possible synergistic interaction of AA genotype with smoking, although the result bears replication in larger samples. Our data suggests that SNPs in the NOS2A gene are associated with increased risk for AMD and might modulate the effect of smoking on AMD.